2014
DOI: 10.1111/jphp.12287
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the cholesteryl ester transfer protein inhibitor evacetrapib on lipoproteins, apolipoproteins and 24-h ambulatory blood pressure in healthy adults

Abstract: ObjectivesWe investigated the safety, tolerability, pharmacokinetics and pharmacodynamics of evacetrapib.MethodsHealthy volunteers received multiple daily doses of evacetrapib (10–600 mg) administered for up to 15 days in a placebo-controlled study.Key findingsMean peak plasma concentrations of evacetrapib occurred at 4–6 h and terminal half-life ranged 24–44 h. Steady state was achieved at approximately 10 days; all subjects had undetectable levels of evacetrapib 3 weeks after their last dose. The trough inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 22 publications
(46 reference statements)
1
24
0
Order By: Relevance
“…The rationale for inhibiting CETP to increase HDL-C dates back to the early 1990s, when genetic studies in Japanese subjects found that individuals with CETP deficiency had increased HDL concentrations (45,46 ). Subsequent clinical studies have evaluated the HDL-raising properties of CETP inhibitors (15,36,(47)(48)(49). For example, treatment with 300 mg evacetrapib raised HDL-C concentrations by Ͼ80% in healthy volunteers, and increased total HDL-C and non-ABCA1-specific cholesterol efflux capacity (CEC) in individuals with mild dyslipidemia (36,(47)(48)(49).…”
Section: The Evolving Role Of Hdl: Rct and Beyondmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale for inhibiting CETP to increase HDL-C dates back to the early 1990s, when genetic studies in Japanese subjects found that individuals with CETP deficiency had increased HDL concentrations (45,46 ). Subsequent clinical studies have evaluated the HDL-raising properties of CETP inhibitors (15,36,(47)(48)(49). For example, treatment with 300 mg evacetrapib raised HDL-C concentrations by Ͼ80% in healthy volunteers, and increased total HDL-C and non-ABCA1-specific cholesterol efflux capacity (CEC) in individuals with mild dyslipidemia (36,(47)(48)(49).…”
Section: The Evolving Role Of Hdl: Rct and Beyondmentioning
confidence: 99%
“…Subsequent clinical studies have evaluated the HDL-raising properties of CETP inhibitors (15,36,(47)(48)(49). For example, treatment with 300 mg evacetrapib raised HDL-C concentrations by Ͼ80% in healthy volunteers, and increased total HDL-C and non-ABCA1-specific cholesterol efflux capacity (CEC) in individuals with mild dyslipidemia (36,(47)(48)(49). In patients with acute coronary syndrome (ACS), treatment with dalcetrapib, another CETP inhibitor, also significantly raised HDL-C, principally via an increase in ABCA1-mediated cholesterol efflux (15,49 ).…”
Section: The Evolving Role Of Hdl: Rct and Beyondmentioning
confidence: 99%
“…In multiple‐dose studies in healthy subjects, evacetrapib increased HDL‐C and decreased LDL‐C and was well‐tolerated at doses up to 600 mg . In a Phase II study in dyslipidemic patients, evacetrapib increased HDL‐C by up to 129% and decreased LDL‐C by up to 36%, and when administered alone or with statins was well‐tolerated .…”
mentioning
confidence: 98%
“…So far, the empirical evidence suggests that elimination of evacetrapib is not affected by treatment duration through 12 weeks of treatment, which is the longest duration studied to date . After a single dose of evacetrapib, the apparent terminal half‐life is about 45 hours (unpublished data) and is the same after 2 weeks of dosing . A single sample was collected for measurement of evacetrapib plasma concentrations 4–6 weeks after the end of 12 weeks of once‐daily treatment.…”
mentioning
confidence: 99%
“…EVC became a hopeful candidate (10,11,12,13,14) for new generation of lipid modifying agents. It belongs to a class of CETP, cholesterylester transfer protein inhibitors.…”
mentioning
confidence: 99%